1997
DOI: 10.1111/j.1432-1033.1997.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determination of the O‐Linked Sialyl Oligosaccharides Liberated from Fetuin with Endo‐α‐N‐Acetylgalactosaminidase‐S by HPLC Analysis and 600‐MHz 1H‐NMR Spectroscopy

Abstract: The endo-a-N-acetylgalactosaminidase from the culture medium of Streptomyces sp. OH-I 1242 (endo-GalNAc-ase-S) hydrolyzed the 0-glycosidic linkage between GalNAc and Ser (Thr) in fetuin, liberating oligosaccharides. The 0-linked oligosaccharides liberated from the fetuin with endo-GalNAcase-S were pyridylaminated following fractionation on a Bio-Gel P-4 column. The structure of the pyridylaminated 0-linked oligosaccharides from fetuin has been determined by reverse-phase HPLC and 600-MHz 'H-NMR spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…As shown in Scheme 1A, human transferrin contains two N-linked complex-type glycans, and the major oligosaccharide has 2 mol of ␣2,6-linked NeuAc (Scheme 1A) (34), whereas bovine fetuin has three N-linked glycans with the major oligosaccharides of a sialylated triantennary complex-type (35), and three O-linked glycans of a sialylated core-type 1 on a molecule, respectively (Scheme 1B) (36,37). Total fetuin glycans contain approximately equal amounts of ␣2,3-and ␣2,6-linked NeuAc residues.…”
Section: Comparison Of Sialic Acid-specific Lectins In the Reactivitymentioning
confidence: 99%
“…As shown in Scheme 1A, human transferrin contains two N-linked complex-type glycans, and the major oligosaccharide has 2 mol of ␣2,6-linked NeuAc (Scheme 1A) (34), whereas bovine fetuin has three N-linked glycans with the major oligosaccharides of a sialylated triantennary complex-type (35), and three O-linked glycans of a sialylated core-type 1 on a molecule, respectively (Scheme 1B) (36,37). Total fetuin glycans contain approximately equal amounts of ␣2,3-and ␣2,6-linked NeuAc residues.…”
Section: Comparison Of Sialic Acid-specific Lectins In the Reactivitymentioning
confidence: 99%
“…All of the enzymes are secretory and high-molecular mass proteins (Ͼ110 kDa), and are able to release Gal␤1,3GalNAc disaccharide from glycoproteins. A similar enzyme was found in the culture medium of Streptomyces sp., which is capable of releasing longer sugar chains than the disaccharide from porcine mucin (18,19), although further studies are necessary to validate its action.Bifidobacteria are strictly anaerobic lactic acid-producing bacteria that constitute a major part of the intestinal microflora of human and animals, and have attracted a great deal of attention because of their many beneficial probiotic effects (20). Recently, we found that bifidobacteria widely have an endo-␣-GalNAcase specific for Core 1 mucin-type O-glycans.…”
mentioning
confidence: 99%
“…The growth of Streptomyces sp. OH-11242 and preparation of PGM were described by Ishii-Karakasa et al [3][4][5] Crude enzyme from the culture fluid. The culture fluid of Streptomyces sp.…”
Section: Methodsmentioning
confidence: 99%
“…The crude enzyme was prepared by 80% (v/v) ammonium sulfate precipitation, gel chromatofocusing, DEAE-Toyopearl and N-(p-aminophenyl)-oxamic-acid-agarose chromatography as previously described. 4 Some of the pooled solution was concentrated by dialysis against poly(ethylene glycol) 20000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation